Petrology of peridotite host basaltic lavas of northern Ngaoundéré (Adamawa plateau, Cameroon, Central Africa) - Ndassa Zénab Nouraan, Njankouo; Oumarou Faarouk, Nkouandou; Jacques-Marie, Bardintzeff; Alexandre Alembert, Ganwa; Mefire Aminatou, Fagny; Arnaud, Tizi (International Journal of Advanced Geosciences, 2019)
Small volcanoes and flows of Cainozoic basaltic lavas, containing numerous mantle peridotite xenoliths, outcrop at northern NgaoundÃ©rÃ© in Adamawa plateau. They are composed of arena of decimeter to meter in size of bowls and blocs of dark matrix, showing crystals of olivine, clinopyroxene and oxides. All lavas present microlitic porphyritic texture with euhedral to subhedral crystals of the same phases drowned in the matrix of the same minerals plus plagioclase microlites.Microprobe analyses show that olivine phenocrysts are relatively Fo-rich (80.9-84.3 %) compared to microphenocrysts and microcrysts (Fo71.1-75.9 %). Olivine xenocrysts are highly magnesian (83.9-89.8 %). Clinopyroxene are diopside and augite. Oxides crystals are Ti-magnetite and plagioclase are labradorite and bytownite.ICP-AES and ICP-MS whole rocks analyses show that the host peridotite basaltic lavas of northern NgaoundÃ©rÃ© are undersaturated basanites of typical alkaline lava series. They seem not contaminated by crustal materials. They are the results of low partial melting rate of the garnet mantle source located at more than 80 km depth. The eruptions of northern NgaoundÃ©rÃ© lavas have been facilitated by Pan African cracks and they have sampled the subcontinental lithospheric mantle as xenoliths at different pressures and depths on their way to the surface.Â Â